Roles for Sorrowing after Loss - Day Before the End of the World by Aleksander Jurewicz and He Passed Away by Inga Iwasiów - Czyżak, Agnieszka (Poznańskie Studia Slawistyczne, 2016)
The main aim of the article is recognition of current manners of transforming deep sorrow after loss of relatives in literature. The theme of two novels written by polish authors – man and woman – in 21st century is death of their fathers. Preparing for funerals intensifies mourning and recalls memories of the past. Those experiences demand expression. Interpretations of two autobiografical novels prove that the traditional roles for sorrowing after loss which were highly dependent on gender, later in 20th century were submitted certain changes and this process accelerate. Strong feelings of mourning belong to human being, The ways of manifesting those feeligs are connected with gender but are not entirely determined by this category.